A proibição da união homoafetiva: uma ameaça à segurança jurídica - Costa, Cícero Pereira da (2025)
The scientific work aims to study the legal setback brought about by the approval of PL 580/2007, which prohibits the Civil Union Contract for Same-Sex Union. For this purpose, a qualitative study was conducted through a bibliographic and documentary review, using sources such as books, articles, legislation, transcripts of public hearings, and news reports. In the first section, the evolution of LGBT rights in Brazil is demonstrated, analyzing the concept of family and stable unions, and the actions and consequences of equating same-sex unions with civil marriage, where legal activism seeks to ensure that the homosexual population has their fundamental rights enforced. Next, the approval of PL 580/2007, which forbids the Civil Union Contract for Same Sex Couples, is analyzed, showing how it deviates from its initial objective. Finally, the legitimacy and stability of same-sex unions are examined in light of the setback of their legal prohibition. It was concluded that, in the absence of a law that prohibits or regulates a certain conduct, this conduct is considered lawful, since the right prevails over the law. However, any attempt to obstruct progress in guaranteeing fundamental rights for individuals in these situations is marked by prejudice rooted in society. After all, homosexuality is an intrinsic part of human life, and in same-sex relationships, there is a right to love and share affection.